Bifid canals: identification of three clinical cases using cone-beam computed tomography images - Paulo de Camargo MORAES; Daniela Prata TACCHELLI; Rubens Gonçalves TEIXEIRA; Luciana Butini OLIVEIRA; José Luiz Cintra JUNQUEIRA (Faculdade São Leopoldo Mandic, 2018)
Anatomical variations of mandibular canal have rarely been reported in the literature. The aim of this paper is to present three clinical cases of bifid mandibular canal diagnosed with cone-beam computed tomography (CBCT) as well as discuss its clinical implications. The first case is very interesting due to its anatomic variation verified in a panoramic radiograph during orthodontic planning, mimicking an odontogenic tumor. The second and the third cases were identified during tomographic evaluation for third molar exodontia. The diagnosis of bifid canals is extremely relevant in order to avoid complications during surgical procedures and implant placement as well as anesthesia failures which cause pain, paresthesia and bleeding. Furthermore, the shape of these anatomical variations can be confused with bone lesions.